THREE-DIMENSIONAL MODELLING OF THERMAL STRESSES IN A PLANAR SOLID OXIDE FUEL CELL OF A NOVEL DESIGN - Zinko, Tomasz; Pianko-Oprych, Paulina; Jaworski, Zdzisław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The presented modelling investigation was carried out to analyze thermal stresses and expansion in an anode supported planar Solid Oxide Fuel Cell (pSOFC). The temperature distribution was based on previously developed thermo-electrochemical model predicting fuel cell operation. The design of a single pSOFC consisted of three ceramic layers of membrane electrode assembly: anode, electrolyte, cathode and two cross-flow bipolar plates with 26 ribs. The gases flowed diagonally from one cell corner to the opposite one. The fuel and air flows were cross-wise opposed on each bipolar plate side. The study allowed to indicate the most vulnerable to thermal damage area of the fuel cell in the operating conditions. The results will be useful in further design modification and performance optimization of the SOFC.